Effects Of Lactobacillus Spp. Against Vaginal Candidiasis In Pregnant Women - Ang, Xin Yee (2022)
This study aimed to investigate the effects of lactobacilli probiotics in preventing the recurrences of vulvovaginal candidiasis (VVC) in 78 pregnant women with VVC (probiotic, n = 39; placebo, n = 39) and the potential benefits on quality of life. The lactobacilli probiotic (SynForU-HerCare; two capsules/day of 9.5 log CFU/capsule) or placebo was administered for 8-weeks in a randomized, double-blind, and placebo-controlled study. Subjects were assessed for vaginal and gut health conditions at week-0, 4, and 8 via questionnaires and analyzed vaginal microbiota and inflammatory changes. The vulvovaginal symptom questionnaire covered vulvovaginal symptoms and quality of life. Probiotic group was exhibited the reduction of irritation (P=0.023) and discharge (P=0.011) starting week-4 and continued after week-8 (P<0.05) as compared to the placebo. Probiotic group was exhibited the reduction of concern about symptoms after week-4 (P=0.010) and continued after week-8 (P=0.001), accompanied by reduced impairment of daily activities (P=0.012) and continued after week-8 (P=0.026). Probiotic group was exhibited the reduction of recurrences of both emotional and social stress compared to the placebo at both week-4 and week-8 (P<0.05). Probiotic group showed higher defecation times per week at week-4 (P=0.010) and week-8 (P=0.001) compared to the placebo group.